Understanding and Creating Art - Goldstein, Ernest, 1933- (St. Paul, Minn : West Pub. Co., 1992)
Discusses some important paintings and sculpture in terms of design elements and also from the viewpoint of the artist. Includes questions and art activities.
Reprint. Originally published: Dallas, Tex. : Garrard Pub. Co., Textbook Division, c1986.
Includes bibliographical references and indexes.
Keywords: Composition (Art) -- Juvenile literature; Visual perception -- Juvenile literature; Art -- Psychology -- Juvenile literature; Art appreciation; Composition (Art); Design